Genetic analysis resolves differential diagnosis of a familial syndromic dilated cardiomyopathy: A new case of Alström syndrome. Issue 7 (12th May 2020) - Lombardo, Barbara; D'Argenio, Valeria; Monda, Emanuele; Vitale, Andrea; Caiazza, Martina; Sacchetti, Lucia; Pastore, Lucio; Limongelli, Giuseppe; Frisso, Giulia; Mazzaccara, Cristina
Abstract: Background: Syndromic dilated cardiomyopathy (DCM) includes a group of complex disorders with a very heterogeneous genetic etiology, leading to delay in definitive diagnosis. Conversely, an early genetic diagnosis is very important in determining the disease course, the prognosis, and may guide personalized treatments and family counseling. Methods: We analyzed two brothers with a multisystemic disorder, including dilated cardiomyopathy, diabetes, bilateral neurosensorial hearing loss, and optic atrophy, using different genetic approaches, namely mitochondrial DNA sequencing, comparative genomic hybridization‐array (a‐CGH) and whole exome sequencing (WES). Results: Sequencing of the wide mitochondrial genome revealed, in both brothers, the known homoplasmic variant rs2853826 in the subunit 3 of the NADH dehydrogenase gene ( MT‐ND3 ), whose pathogenicity was conflicting. Comparative genomic hybridization‐array analysis revealed in both patients and their father two heterozygous deletions in Phosphodiesterase 4d‐Interacting Protein ( PDE4DIP ) and Protocadherin‐related 15 ( PCDH15) genes, respectively. The use of WES detected a pathogenetic mutation in ALMS1, enabling the definitive diagnosis of Alström syndrome. Conclusion: We demonstrated how the diagnosis of a complex heterogeneous disease may be difficult, due to several overlapping manifestations and the possible interaction of more genetic variants that could lead to a more severe and complex phenotype. This paper strongly evidences how genomics is revolutionizing the diagnosis of rare complex disease, representing one of the most essential steps to enable a definitive diagnosis and to establish the etiology for diseases, such as syndromic DCM. Abstract : The diagnosis of a complex heterogeneous disease may be difficult, due to several overlapping manifestations and the possible interaction of more genetic variants. By using different genetic approaches we obtained a definitive diagnosis of Alström syndrome in two brothers with a multisystemic disorder.